Study of the antidyskinetic effect of eltoprazine in animal models of levodopa‐induced dyskinesia. Issue 8 (6th February 2013) - Bezard, Erwan; Tronci, Elisabetta; Pioli, Elsa Y.; Li, Qin; Porras, Gregory; Björklund, Anders; Carta, Manolo
<x xml:space="preserve">Abstract</x> The serotonin (5‐hydroxytryptamine [5HT]) system has recently emerged as an important player in the appearance of l‐3, 4‐dihydroxyphenylalanine (levodopa [l‐dopa])–induced dyskinesia in animal models of Parkinson's disease. In fact, dopamine released as a false transmitter from serotonin neurons appears to contribute to the pulsatile stimulation of dopamine receptors, leading to the appearance of the abnormal involuntary movements. Thus, drugs able to dampen the activity of serotonin neurons hold promise for the treatment of dyskinesia. The authors investigated the ability of the mixed 5‐HT 1A/1B receptor agonist eltoprazine to counteract l‐dopa–induced dyskinesia in 6‐hydroxydopamine‐lesioned rats and in 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP)‐treated macaques. The data demonstrated that eltoprazine is extremely effective in suppressing dyskinesia in experimental models, although this effect was accompanied by a partial worsening of the therapeutic effect of l‐dopa. Interestingly, eltoprazine was found to (synergistically) potentiate the antidyskinetic effect of amantadine. The current data indicated that eltoprazine is highly effective in counteracting dyskinesia in preclinical models. However, the partial worsening of the l‐dopa effect observed after eltoprazine administration represents a concern; whether this side effect is due to a limitation of the animal models or to an intrinsic property of eltoprazine needs to be addressed in ongoing clinical trials. The data also suggest that the combination of low doses of eltoprazine with amantadine may represent a valid strategy to increase the antidyskinetic effect and reduce the eltoprazine‐induced worsening of l‐dopa therapeutic effects. © 2013 Movement Disorder Society